Books and social media how the digital age is shaping the printed word - Johnson, Miriam J. (Routledge, an imprint of the Taylor & Francis Group, 2022)
"Social media and digital technologies are transforming what, and how, we read. Books and Social Media considers the way in which readers and writers come together in digital communities to discover, and create, new works of fiction. This new way of engaging with fiction stretches the boundaries of what has been considered a book in the past, by moving beyond the physical, or even digitally, bound object to the consideration of content, containers, and the ability to share. Using empirical data and up-to-date research methods, Miriam Johnson introduces the ways in which these digitally social platforms give rise to a new type of citizen author who chooses to sidestep the industry's gatekeepers and share their works directly with interested readers on these social platforms. Gender and genre, especially, play a key role in developing the communities in which these authors write. The use of surveys, interviews, and data mining brings to the fore issues of gender, genre, community, and power which highlight the push and pull between these writers and the industry. Questioning what we always thought we knew about what makes a book, and traditional publishing channels, this book will be of interest to anyone studying or researching publishing, book history, print cultures, digital and contemporary literatures."--Provided by publisher.